The Perceived Probability of Job Loss and Future Labour Market Outcomes - Hahn, M; Wooden, M; McGuiness, S (My University, 2014)
Longitudinal survey data are used to test the degree to which worker expectations of future job loss are correlated with changes in labour market status. Three major findings are reported. First, perceived probabilities of expected job loss are only weakly related to both exogenous job separations and subsequent transitions to unemployment and inactivity. Second, while fears of job loss tend to persist across time and job spells, they do so at a highly diminishing rate. Third, quit intentions are strongly correlated with both voluntary separations and transitions to alternative employment, and do not diminish greatly across successive employment spells.
Keywords: Employment -- Exit from employment (Retirement/Redundancy); Ageing; Labour market; Employment; Exit from employment (Retirement/Redundancy); Ageing; Employment and unemployment